Tempero baiano no desenvolvimento urbano: análise de competitividade do segmento empresarial da alta gastronomia de Salvador - COSTA, Paulo Patrício (2013)
This paper refers to a study that sought to identify the degree of competitiveness of the enterprise segment of the haute cuisine of the city of Salvador, in the period between the years 2010 and 2012. This study adopted in a descriptive qualitative methodology with semi-structured research approaches adapted in Porter’s structural analysis of industry (1999), which supports the principal theoretical references. Sought support from ontological, religious and historical landmarks for analysis in gastronomy, innovation, and aspects of its founding entrepreneurial initiatives. Adopts a theoretical complement to Schumpeter (1982) for innovation and entrepreneurship, Brillat-Savarin (2009) for the birth of modern commercial gastronomy, Christaller (1933) for location and spatial occupation in the dynamics of strategic business choices and Maslow (1970) in the identification of target geo-socio-economic-psychographic-age of haute cuisine. The investigation revealed a segment of haute cuisine "in training", identified that the segment has a high degree of competitiveness, with low resistance to new entrants. Additionally an investigation revealed a reasonable symmetry among industrialists regarding the criteria for definition of haute cuisine, citing 26 criteria as indispensable, and (referred to in this paper as “the A to Z of haute cuisine”. In this work suched systematizations new to the business segment of high gastronomy, as the stages of maturing markets, the hierarchical pyramid of human needs from the perspective of gastronomy, and a model calculation of weighted demand.